PENGARUH MODEL LEARNING CYCLE “5E” TERHADAP HASIL BELAJAR IPA TEMA I SUB TEMA I SISWA KELAS VI DI SDN 17 SITIUNG KABUPATEN DHARMASRAYA - Ovi Andini; Riyadi Saputra; Suci Rahma Putri (Dharmas Education Journal (DE_Journal), 2021)
This research is motivated by the low learning outcomes of students in grade VI SDN 17 Sitiung. One effective way to overcome this problem is to use the “5E” Learning Cycle model, this study aims to determine the effect of the “5E” Learning Cycle model on student learning outcomes. This study uses a pre experimental design method in the form of one group pretest. The population in this study was grade VI students with a total of 20 students, the sampling technique was non-probability sampling saturated (census) technique. The data collection technique was carried out by giving a pretest, then continued with treatment and then posttest, the data analysis technique used SPSS 20. The result showed that there was a significant effect on the Learning Cycle “5E” model on the learning outcomes of sixth grade students at SDN 17 Sitiung Dharmasraya regency, with a significance level of 0,000<0,05 meaning H0 was rejected and Ha was accepted.